Pengaruh Self Efficacy Dan Lingkungan Keluarga Terhadap Hasil Belajar Akuntansi Siswa Fase E Di SMK Negeri 2 Padang - Alroy Gumolili; Caterina Lo; Dessyta Gumanti (Kilau Publishing, 2025)
This study aims to analyze: (1) the effect of self efficacy on the accounting learning outcomes of Phase E students at SMK Negeri 2 Padang, (2) the effect of family environment on the accounting learning outcomes, and (3) the simultaneous effect of self efficacy and family environment. This research employs a quantitative approach. The population consists of 144 Phase E accounting students, with 59 selected using the Slovin formula and stratified random sampling. Data were obtained through a validated and reliable questionnaire. Analysis techniques include descriptive and inferential statistics, covering normality, linearity, and multicollinearity tests, followed by multiple linear regression, t-test, F-test, and the coefficient of determination (R²), processed using SPSS version 25.Results show: (1) self efficacy has a positive and significant effect on accounting learning outcomes t-value 16.993 > t-table 2.003, significance 0.000 < 0.05), meaning higher self efficacy improves outcomes. (2) The family environment also has a positive and significant effect t-value 3.123 > t-table 2.003, significance 0.003 < 0.05), indicating its role in enhancing performance. (3) Simultaneously, self efficacy and family environment significantly affect learning outcomes F-value 147.521 > F-table 3.16, significance 0.000 < 0.05), with R² = 83.7%, leaving 16.3% influenced by other factors.